Genius and Demographics in Modern Jewish History - Stern, Eliyahu (The Jewish quarterly review, 2011)
Elijah ben Solomon (1720-1797) and Moses Mendelssohn (1729-1786) are often represented as two poles of eighteenth-century Jewish history: "the Gaon" (Elijah of Vilna) as the defender of rabbinic or "traditional" Judaism, and the "Jewish Socrates" (Mendelssohn), as the founder of "modern" Judaism. A comparative examination of their geniuses in their respective cultural contexts, however, suggests that it was the Gaon who called into question the canons of rabbinic authority, while Mendelssohn tirelessly defended the legitimacy of the rabbinic tradition to his German-speaking audiences. Mendelssohn mobilized his defense of the rabbinic tradition precisely because he was fighting for the political recognition of German Jewry (as followers of rabbinic Judaism). Mendelssohn's argument for pluralism and emancipation of a minority religious group inspired nineteenth-century Western European Jews, who lived as minorities—those who traded their belief in messianic redemption for citizenship in the nation-state, climbed over the ghetto walls of the kehilah (the pre-modern Jewish governing structure) for the freedom of the coffee houses, and turned their backs on the heder and enrolled in universities. Conversely, the Jewish demographic strength and residential propinquity of late eighteenth-century Vilna Jewry allowed the Gaon to question the rabbinic tradition—a position that Mendelssohn would have considered as detrimental to the cause of Jewish emancipation or perhaps even sacrilege. The Gaon's Jewish genius and political agency inspired nineteenth-century Eastern European Jews who lived as majorities—those who left their homes to study with their peers in the privatized Yeshiva, thumbed their nose at the Russian State by boarding boats to Palestine, and joined other anti-Statist political movements.